2015
DOI: 10.1021/acs.orglett.5b02934
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Study on Antihypercholesterolemic Agent Phomoidride: General Biogenesis of Fungal Dimeric Anhydrides

Abstract: To elucidate the general biosynthetic pathway of fungal dimeric anhydrides, a gene cluster for the biosynthesis of the antihy-percholesterolemic agent phomoidride was identified by heterologous expression of candidate genes encoding the highly reducing polyketide synthase, alkylcitrate synthase (ACS), and alkylcitrate dehydratase (ACDH). An in vitro analysis of ACS and ACDH revealed that they give rise to anhydride monomers. Based on the established monomer biosynthesis, we propose a general biogenesis of dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
86
2
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(95 citation statements)
references
References 34 publications
2
86
2
5
Order By: Relevance
“…The polyketide is presumably released from the PKS by the BfL1 hydrolase, although it is not yet known whether this is as the free acid or as a CoA‐thiolester. This result contrasts with the recently reported work of Oikawa, who showed that the hydrolase did not appear to be required in the case of a Talaromyces PKS 18. However it is known that some iterative fungal PKSs, for example the squalestatin tetraketide synthase,23 can release polyketides without the requirement for a dedicated thiolesterase.…”
contrasting
confidence: 76%
See 4 more Smart Citations
“…The polyketide is presumably released from the PKS by the BfL1 hydrolase, although it is not yet known whether this is as the free acid or as a CoA‐thiolester. This result contrasts with the recently reported work of Oikawa, who showed that the hydrolase did not appear to be required in the case of a Talaromyces PKS 18. However it is known that some iterative fungal PKSs, for example the squalestatin tetraketide synthase,23 can release polyketides without the requirement for a dedicated thiolesterase.…”
contrasting
confidence: 76%
“…Heterologous expression experiments utilizing the three genes from one of the T. stipitatus BGCs allowed the isolation of a longer‐chain decarboxylated monomer. These experiments confirm the polyketide/oxaloacetate origin of maleidride monomers 18. However the proteins responsible for the key cyclisation reaction necessary for maleidride biosynthesis remain unkown.…”
supporting
confidence: 54%
See 3 more Smart Citations